A Review of Transparent Conducting Films (TCFs): Prospective ITO and AZO Deposition Methods and Applications - Jessica Patel; Razia Khan Sharme; Manuel A. Quijada; Mukti M. Rana (Nanomaterials)
This study offers a comprehensive summary of the current states as well as potential future directions of transparent conducting oxides (TCOs), particularly tin-doped indium oxide (ITO), the most readily accessible TCO on the market. Solar cells, flat panel displays (FPDs), liquid crystal displays (LCDs), antireflection (AR) coatings for airbus windows, photovoltaic and optoelectronic devices, transparent p–n junction diodes, etc. are a few of the best uses for this material. Other conductive metals that show a lot of promise as substitutes for traditional conductive materials include copper, zinc oxide, aluminum, silver, gold, and tin. These metals are also utilized in AR coatings. The optimal deposition techniques for creating ITO films under the current conditions have been determined to be DC (direct current) and RF (radio frequency) MS (magnetron sputtering) deposition, both with and without the introduction of Ar gas. When producing most types of AR coatings, it is necessary to obtain thicknesses of at least 100 nm and minimum resistivities on the order of 10−4 Ω cm. For AR coatings, issues related to less-conductive materials than ITO have been considered.